Nutritional evaluation of the lipid fraction of Iberian red deer (Cervus elaphus hispanicus) tenderloin. - Quaresma, M a G; Trigo-Rodrigues, I; Alves, S P; Martins, S I V; Barreto, a S; Bessa, R J B (Meat science, 2012)
The meat lipid fraction of psoas major muscle from 20 adult (10 males and 10 females) feral Iberian red deer (Cervus elaphus hispanicus) was characterized by quantification of total fat, total cholesterol, vitamin E and fatty acid (FA) composition, including detailed trans octadecenoate isomers and conjugated linoleic acid (CLA) isomeric profile. The total lipid content revealed a very lean meat (0.99 g/100g of meat), with total cholesterol content averaging 55.6 mg/100g of muscle. The FA profile displayed a very high PUFA level for ruminant meat (30.2g/100g FA). The 18:2 cis-9,trans-11 content was fairly low (0.26% of total FA) compared with other ruminant meats. The comparison of stags and hinds showed more similarities than differences. Nevertheless, hinds displayed superior contents of α-tocopherol and trans MUFA and a better n-6/n-3 ratio than stags.
Keywords: cervus elaphus hispanicus; Cholesterol; CLA; Fatty acid profile; meat quality; Vitamin E